Examen especial a la cartera vencida de C.A ECUATORIANA DE CERÁMICA de la ciudad de Riobamba, período 2020. - Marín Caicedo, Karina Liseth (2023)
The current research work was carried out in order to determine the reasonability of the accounts receivable component of ECUATORIANA DE CERAMICA A.C. company during 2020. The company does not have an updated collection policy management manual; thus, it causes an increase in overdue portfolio as well as lack of liquidity in the company. This special examination will help to define the objectives and methodology of the study through real events which happened in the company. For this, it was necessary to apply the mixed deductive and inductive method.